2015
DOI: 10.1038/srep09444
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum cytokeratin 19 fragments (Cyfra 21-1) in patients with non-small cell lung cancer

Abstract: The role of serum CYFRA 21-1 level in patients with non-small cell lung cancer (NSCLC) remains to be defined. To re-evaluate the impact of serum CYFRA 21-1 in NSCLC survival, we performed this meta-analysis. Databases were searched to identify relevant studies reported after the publication of a meta-analysis in 2004. Totally, 31 studies with 6394 patients were included in this meta-analysis. The pooled Hazard ratios (HRs) indicated that high CYFRA 21-1 level was associated with poor prognosis on overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…This is in agreement with previous studies that reported that early reduction in CYFRA 21-1 is associated with improved NSCLC treatment response. 35 , 37 , 38 , 39 Very few studies have established the prognostic effect of baseline CYFRA 21-1 in SCLC patients. 40 , 41 Although our study only included 16 SCLC patients (20.5%), it suggests the potential utility of this marker, when quantified early during treatment, in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies that reported that early reduction in CYFRA 21-1 is associated with improved NSCLC treatment response. 35 , 37 , 38 , 39 Very few studies have established the prognostic effect of baseline CYFRA 21-1 in SCLC patients. 40 , 41 Although our study only included 16 SCLC patients (20.5%), it suggests the potential utility of this marker, when quantified early during treatment, in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that the biomarkers cytokeratin 19 fragment (CYFRA 21-1) and human epididymis protein 4 (HE4) may be useful in the diagnosis, prognosis, and treatment monitoring of NSCLC [21][22][23][24][25][26][27][28][29][30][31]. These biomarker levels appear to be higher in patients with advanced disease, those with nodal and/or distant metastases, and in those with a poor performance status [27,32,33], with the majority of data regarding the prognostic utility of these biomarkers reported in the advanced disease setting [21,22,24,[28][29][30][31] or across all stages of disease [25,34,35]. However, some evidence exists for CYFRA 21-1 in early-stage NSCLC [36][37][38], including findings from a retrospective analysis of 515 patients with NSCLC who underwent surgery, which showed that in patients with stage I disease, 3-year survival rates were lower in patients with elevated preoperative serum levels of CYFRA 21-1 than in those with normal CYFRA 21-1 levels (60.2% versus 78.4%; p = 0.015) [39].…”
Section: Introductionmentioning
confidence: 99%
“…NSE is reportedly a sensitive tumor marker for neuroendocrine tumors [ 15 ], but the NSE level was within the reference range in the present case. Although CYFRA is a sensitive marker for non-small-cell lung cancer [ 16 ], it was a very sensitive marker for progression and metastases in the present case (Fig. 7 ).…”
Section: Case Presentationmentioning
confidence: 59%